Rules and Discretion in International Economic Policy - Guitian, Manuel (Washington, D.C. : International Monetary Fund, 1992)
Economic interdependence offers the potential for raising global welfare, but there is a fuzzy boundary between national interests and global objectives in the economic policy area. This paper examines the boundary area. It concludes that all international economic regimes must entail a mix of rules and discretion, and it considers the most appropriate weights to be given to rules and discretion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet